MINAWISATA DI WADUK RIAM KANAN KABUPATEN BANJAR - Rizqi, Muhammad Dwi; Andini, Dila Nadya (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
The water tourism sector in Banjar Regency is relatively small even though the geographic potential in the Banjar Regency area is very supportive for the development of water tourism. One of them is the Riam Kanan Reservoir area in Aranio District, Banjar Regency. Riam Kanan Reservoir has vast water potential and can be developed as a tourist destination. The existence of floating net cages (KJA) in this reservoir can also be a tourist attraction. Apart from that, another potential is the existence of Pine Island ecotourism which is currently not optimal due to constraints on the slow development of tourist areas. This writing aims to solve problems and respond to the potential that exists in the Riam Kanan Reservoir by preparing a concept for designing water tourism, namely mina wisata. The aim of designing this tourist attraction is to maximize the potential of the Riam Kanan Reservoir as a water tourism area and develop floating net cages (KJA) as well as interacting with the Pine Island Ecotourism area around the site. The step to achieve the goal is with a tourism design concept that emphasizes water tourism activities and floating net cage (KJA) areas as education and the principle of mutual support with Pine Island Ecotourism through a symbiotic architectural approach. The result is the development of tourist facilities towards the education and tourism sectors through the Edu-Tourism concept as a form of responding to problems in the design of mina wisata.